ANTI-ATHEROSCLEROTIC ACTIVITY OF ELAEOCARPUS GANITRUS ROXB. IN CHOLESTEROL-FED RABBITS - Jain, PRATIBHA K; Sharma, Priyanka; Joshi, Suresh C (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Atherosclerosis was experimentally induced in New Zealand white male rabbits by cholesterol feeding for 120 days for investigating effects of 70% ethanolic Elaeocarpus ganitrus seed extract (EEGS) against atherosclerosis. Methods: Anti-atherosclerotic activity of E. ganitrus extract was evaluated at a dose level of 250 and 500 mg/kg of body weight (p.o). On 121st day, the animals were sacrificed to collect the aorta for determining tissue lipid profile, antioxidant parameters, and histopathological changes. One-way ANOVA followed by Tukey's multiple comparison test was used for the statistical analysis. Results: Aorta of cholesterol-fed rabbits for 120 days showed marked elevation in total cholesterol, triglycerides, and phospholipids. EEGS extract treatment significantly (p≤0.01, ≤0.001) corrected disturbed lipid profile in cholesterol-fed rabbits in a dose-dependent manner during the 60 days of the treatment period. A significant reduction in lipid peroxidation and a considerable raise in glutathione, catalase, and superoxide dismutase levels (p≤0.01, ≤0.001) were accompanied by post-treatment with EEGS extract to cholesterol-fed rabbits. The histopathological modifications such as accumulation of foam cells, atheromatous plaque formation, and lumen size reduction supported the successful induction of atherosclerosis in rabbits. The treated rabbits showed significant protective effect by lowering the deposition of cholesterol and increasing the lumen size compared to cholesterol-fed group. Conclusions: Phytoconstituents such as alkaloids, tannins, flavonoids, steroids, triterpenoids, and carbohydrates in the ethanolic extract may be attributed to effective anti-atherosclerotic and antioxidant activity of plant extract. Our study exhibited that EEGS extract could be a potent herbal therapeutic agent for the treatment of atherosclerosis and hypercholesterolemia-related diseases.